I promise to be faithful : Christian non-Christian interfaith couples and social capital in Singapore - Chee, Glenn (2014)
Christianity in Singapore is interesting as it is a Western religion among Asian religions in an Asian country. Even more intriguing is has been the community’s ability to grow considerably and hold a significant share of the country’s wealth. A factor that could contribute to this growth of the Christian community is the Christian conviction of evangelism. However, Christians in interfaith relationships tend to be more liberal in their practice of Christianity and neglect evangelism. Through in depth interviews with interfaith spouses, this study provides insight into the social capital of Christianity in Singapore and the consequences of contravening Christian norms.